The 86-kD subunit of Ku autoantigen mediates homotypic and heterotypic adhesion of multiple myeloma cells. - Teoh, G (1998)
Previous studies have shown that triggering multiple myeloma (MM) cells via CD40 induces IL-6-mediated autocrine growth as well as increased expression of cell surface adhesion molecules including CD11a, CD11b, CD11c, and CD18. In this study, we generated the 5E2 mAb which targets an antigen that is induced upon CD40 ligand (CD40L) activation of MM cells. Immunofluorescence, immunoprecipitation, and protein sequencing studies identified the target antigen of 5E2 mAb as the 86-kD subunit of the Ku autoantigen. We demonstrate that increased cell surface expression of Ku on CD40L-treated cells is due to migration of Ku from the cytoplasm to the cell surface membrane. Moreover, cell surface Ku on CD40L-treated MM cells mediates homotypic adhesion of tumor cells, as well as heterotypic adhesion of tumor cells to bone marrow stromal cells and to human fibronectin; and 5E2 mAb abrogates IL-6 secretion triggered by tumor cell adherence to bone marrow stromal cells. These data suggest that CD40L treatment induces a shift of Ku from the cytoplasm to the cell surface, and are the first to show that Ku functions as an adhesion molecule. They further suggest that cell surface Ku may play a role in both autocrine and paracrine IL-6-mediated MM cell growth and survival.